Disappearing Text as a Clinical Decision Support Layer: A Case Series - Silberlust, Jared; Small, William; Shah, Darhsi; Chakravartty, Eesha; Moawad, Katherine; Moawad, Andrew; Testa, Paul; Feldman, Jonah (Applied Clinical Informatics, 2025)
This case series aims to evaluate several applications of inline disappearing text (DT) clinical decision support (CDS) tools within clinician documentation.DT blocks were created to prompt documentation for perioperative anticoagulation planning (scenario 1), predischarge intravenous antibiotic planning (scenario 2), and advanced care planning (ACP; scenario 3). In scenario 1, DT was the only intervention. In scenario 2, DT was paired with a documentation SmartList. In scenario 3, DT was paired with a documentation SmartList and an OurPractice advisory. The number of documented perioperative anticoagulation plans, predischarge intravenous antibiotic plans, and ACP notes was measured pre- and postintervention and compared using chi-square analyses.In scenario 1, there was no statistically significant change in the percentage of perioperative anticoagulation plans documented at 0 to 24 and 24 to 48 hours before surgery. In scenario 2, documentation of antibiotic contingency planning in patients expected to be discharged within 24 hours increased from 60% (54/90 notes) to 93% (1,850/1,994 notes) X2 (1, n = 2,084) = 113.1, p < 0.001. In scenario 3, ACP note documentation by discharge in patients with a positive mandatory surprise question increased from 43% (821/1,909 encounters) to 52% (975/1,874 encounters) X2 (1, n = 3,783) = 30.5, p < 0.001.Utilizing DT in conjunction with other forms of CDS was associated with an improvement of documentation quality in predischarge IV antibiotics and ACP. A sociotechnical analysis explores how interactions between technology, people, workflow, and culture could contextualize how utilizing DT with other forms of CDS was more effective than DT alone.
Keywords: clinical decision support; socio-technical aspects of information technology; clinical documentation and communications; inpatient care; human–computer interaction